2005
DOI: 10.1097/01.nmd.0000177788.25357.de
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Social Cognition and Insight in the Prediction of Inpatient Violence Among Individuals With a Severe Mental Illness

Abstract: The purpose of this study was to assess the utility of social cognition and insight in the prediction of violence in a psychiatric inpatient sample. Violence history, demographic information, symptomatology, neuropsychological functioning, social cognition (i.e., attributional style), and insight were assessed in 29 inpatients with severe mental illness. Greater posttest violence was associated with greater pretest violence, less education, greater psychiatric distress, neuropsychological impairment, and hosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 45 publications
4
37
0
3
Order By: Relevance
“…For example, a review published by Couture et al 15 established an association between community functioning and different domains of social cognition (social perception, emotion perception and Theory of Mind). It has been even suggested that social cognition may be more relevant for functional outcome than neurocognition 28,34,42 . Thus, the Fett et al 28 meta-analysis studying the relationship of neurocognition and social cognition with different functional outcome domains in schizophrenia found that social cognition was more related to community functioning than neurocognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a review published by Couture et al 15 established an association between community functioning and different domains of social cognition (social perception, emotion perception and Theory of Mind). It has been even suggested that social cognition may be more relevant for functional outcome than neurocognition 28,34,42 . Thus, the Fett et al 28 meta-analysis studying the relationship of neurocognition and social cognition with different functional outcome domains in schizophrenia found that social cognition was more related to community functioning than neurocognition.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in the last years have also associated social cognition with functioning, so that social cognitive performance would explain an additional proportion of the variance of functioning that is not explained by neurocognition 16, [34][35][36][37][38][39][40][41][42] . Some studies have even found that social cognition could be a better predictor of functioning than neurocognition itself 29, 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of social cognition in schizophrenia have shown the following: Social cognition predicts functional outcomes independently from, and perhaps more strongly than, neurocognition [15][16][17][18][19][20][21]; social cognition is related to the severity of the disorder and rates of relapse [22][23][24]; negative and disorganized symptoms are related to low social competence, difficulty in social representations, and poor social and vocational adjustment [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]; there is a significant association between social cognition and quality of life (QoL) [26,27]; and social cognitive skills play an important role in patients' subjective evaluation of their own QoL [28]. Finally, as Tas et al [27] recently reported, ''the association between mental state reasoning and the more internal aspect of QoL in schizophrenia may reflect a specific role for social cognition in introspective and subjective judgments of one's own QoL, whereas neurocognition and negative symptomatology may be more predictive of the external or extrinsic aspect of QoL.…”
Section: Introductionmentioning
confidence: 98%
“…This was true at 10-, 15-, and 20-year periods. Specific clinical findings with regard to forensic patients, the violence triad, and victimization of women as well as methodological issues were discussed and the implications noted.Psychiatric patient assaults on health care staff are a serious and continuing occupational hazard [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In 1995, Bjorkley and his colleagues estimated that 15-30% of hospitalized patients engaged in assaults and that the prevalence of aggressive behavior ranged from 0.15 assaults per bed year to as high as 88.8 incidents per bed year in some high security units [2].…”
mentioning
confidence: 99%